RISK FACTORS OF LUNG ADENOCARCINOMA IN PATIENTS AT DR. SOETOMO DISTRICT GENERAL HOSPITAL SURABAYA IN 2018 - Luluk Lady Laily; Santi Martini; Kurnia Dwi Artanti; Sri Widati (Universitas Airlangga, 2020)
Lung adenocarcinoma is one type of lung cancers that increases in number every year globally. Smoking is one of the risk factors for lung adenocarcinoma. This study aimed to determine the distribution of the risk factors of lung adenocarcinoma in patients. The risk factors observed in this study included age, gender, smoking history, number of cigarettes, types of cigarettes, and smoking duration. This study was descriptive and performed a cross sectional design. The study’s population was all lung cancer patients who were treated at Dr. Soetomo District General Hospital Surabaya. The samples were drawn using the accidental sampling technique from the population that met the inclusion criteria. The inclusion criteria for this respondents were patients who were diagnosed with lung adenocarcinoma and were willing to be interviewed. While the exclusion criteria involved patients with incomplete medical record data and patients who were not willing to be interviewed. The results indicate that the majority of lung adenocarcinoma patients at Dr. Soetomo District General Hospital Surabaya were male who were light smokers, diagnosed at more than 50 years old. Most of them used filter cigarettes and had smoked for more than 30 years. Keywords: Lung adenocarcinoma, risk factors, cross-sectional.